The Interrogation of Experts and Specialists in the Civil Proceeding (Recomendations to the Expert, the Court, the Parties' Representatives) - M. V. Zhizhina (Теория и практика судебной экспертизы, 2016)
Interrogation of the expert is very significant difficulty for the subjects of interrogation, as the plaintiff, the defendant and the court are not well versed in the area of knowledge possessed by the expert. It is not always tactically ready and competent experts for the implementation of this procedural action. However, it is an expert- Interrogation helps to assess the probative value of its conclusion. This article presents some tactical recommendations Interrogation of experts and specialists in civil and arbitration processes, knowledge and observance of which will be useful both to the court and the representatives of the parties and experts.